PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL MEDIASI - Hatta Setiabudhi (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
The purpose of this study was to determine the mediating role of stock prices in the influence of profitability and firm size on firm value. Stock prices use the closing price in the capital market, profitability uses return on assets (ROA), company size uses the natural logarithm of Total Assets, while company value uses price to book value (PBV). The population in this study are mining sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample used as many as 12 companies. The sampling technique used purposive sampling method. The testing technique uses Partial Least Squares - Structural Equation Model (PLS-SEM) using SmartPLS v.3.3.7. This study shows that profitability has a positive and significant effect on stock prices, firm size has a negative and significant effect on stock prices, profitability has no direct effect on firm value. Firm size directly has a positive and significant effect on firm value. Stock prices have a positive and significant effect on firm value. As for the indirect effect, stock prices are not able to mediate the effect of profitability on firm value and stock prices are able to mediate firm size on firm value.